The Contribution of Ibn Arabi’s Sufism-Philosophical Thought to The Concept of Perfect Human Being who Rationally Believes - Putra, Merry Christian; Widodo, Agus (Journal of Asian Orientation in Theology, 2024)
Ibn Arabi was one of the great Islamic thinkers who lived between 1165-1240 AD. He was known as one of the highest Sufi master (mystic) in human spiritual achievement with title Sheikh al-Akbar (Doctor Maximus or The Great Master). Using the library research, this article aims to explore and find the contribution of Ibn Arabi’s Sufism-philosophical thought and find its relevance to realize the perfect human being, equipped with rational faith. The results show that Ibn Arabi succeeded in “marrying” philosophy with Islamic teachings so that he can be categorized as a Sufi-philosopher and his thought has a Sufism-philosophical character. This style of thought is very relevant to help modern people who have a tendency to separate faith from ratio. For Ibn Arabi, human perfection lies in being together with God. However, this togetherness with God must be understood and lived rationally. In other words, a perfect human being is one who believes in God rationally.